Penelitian sistem klasifikasi di perpustakaan melalui database Google Scholar: Narrative literature review - Awaliyah, Annisa; Khairul Anwar, Rully; Chaerani Djen Amar, Siti; Nursanti Rukmana, Evi (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2023)
Classification is the activity of grouping or collecting similar objects and separating objects that are not the same, to be arranged into a systematic sequence. In the library, the arrangement of library materials in the library is never separated from the implementation of a classification system that functions as a separator in grouping collections on shelves, as well as a systematic arrangement that will make it easier for librarians. and library users to search and retrieve collections in the library. This study aims to determine the research classification system in the library through the Google Scholar database which analyzes research themes/topics, research methods, and research results used. This study uses the narrative literature review method for references related to the topic of the library classification system with the number of references analyzed in ten references indexed by the Google Scholar database with publication ranges from 2015 to 2022. The results show that the classification system is very important for libraries because the existence of a classification system is very helpful for librarians in processing collection data and also makes it easier for librarians and users to find retrieval. The classification systems used in various libraries or information institutions are: Dewey Decimal Classification, Universal Decimal Classification, Colon Classification, and Library of Congress Classification.